Curcumin Modulates PTPRZ1 Activity and RNA m6A Modifications in Neuroinflammation‐Associated Microglial Response - Ninan Zhang; Ruifan Lin; Wenya Gao; Honglin Xu; Yuejia Li; Xiahe Huang; Yingchun Wang; Xianghong Jing; Wenxiang Meng; Qi Xie (Advanced Science)
Abstract Neuroinflammation is often characterized by an overactive microglial response. Curcumin, known for its anti‐inflammatory and antioxidant properties, can mitigate microglial hyperactivity following epileptic seizures. The study delves into the molecular mechanisms underlying curcumin's modulation of RNA post‐transcriptional N (6)‐methyladenosine (m6A) modification. It is found that curcumin interacts with the Z1‐type protein tyrosine phosphatase receptor (PTPRZ1), maintaining its enzymatic activity and thus regulating the phosphorylation of the m6A‐reader YTH domain‐containing family protein 2 (YTHDF2). This modulation affects the expression of critical genes, resulting in reduced inflammatory responses. These findings highlight the importance of post‐transcriptional modifications of RNA in the neuroprotective and anti‐inflammatory effects of curcumin, offering new insights for the treatment of related diseases.